Sustainable future of waqf assets: A proposed assessment model based on environmental design and green architectural principles - Keskin, Goekhan; Daggulu, Ibrahim Barak (GAZI UNIV, FAC ENGINEERING ARCHITECTURE, 2025)
Foundations represent the institutionalized form of the age-old spirit of mutual aid and solidarity throughout history. Many services that are currently provided by modern states and private enterprises were previously carried out through foundations. Foundations that have been handed down from the Seljuk and Ottoman periods to the present day, but with no administrators left, are managed and represented by the General Directorate of Foundations. The General Directorate of Foundations is tasked with both revitalizing foundation cultural heritage and overseeing the construction of new buildings during property evaluations. In this study, concepts such as sustainability, building information modeling, green building certification systems will be examined in order to find an answer to the question of what should be done in order for the foundation immovables to be newly created to be the foundation cultural assets of the future and the existing foundation cultural assets to be restored according to the principles of sustainability. As a result of the examination and research, a road map and framework will be drawn and a model proposal will be made for the production and restoration of foundation immovables in line with the principles of sustainability. The model covers foundation immovables evaluated by real estate evaluation methods. Finally, some investment projects that have already been implemented on this model will be analyzed. In order to obtain accurate results, 20 examples from different regions of Istanbul and different building types have been selected and evaluated, and 4 of the examples will be presented within the scope of the study. The results of the study show that it is possible and necessary to adopt and apply sustainability principles for the management and development of foundation immovables.
Keywords: Sustainable architecture; Certification systems; Building information modeling; Foundations; Foundation cultural assets; Engineering